INOVASI PENGELOLAAN SAMPAH OLEH KELOMPOK BANK SAMPAH : - Musadad, Anwar; Suhaya, Suhaya; Zihan, Zihan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The purpose of this research is to provide input for the development of more effective waste management policies, supporting the empowerment of women, particularly female-headed households. In addition to processing waste, the Kartini Waste Bank also creates livelihoods through sorting, recycling, and selling value-added products. This research employs a qualitative approach. Through this approach, researchers will directly visit the Kartini Waste Bank to describe the waste management process in the field using an interactive model. The results of the application of the 3R principles of Reduce, Reuse, and Recycle serve as an educational tool for behavioral change in the community through waste management activities. The Kartini Waste Bank is an effort to increase community participation and maintain environmental cleanliness. This study also describes women's leadership in guiding the Kartini Waste Bank organization to develop through program innovations. Furthermore, researchers will conduct future research on women's roles in other organizations. Furthermore, a study will examine women's involvement in influencing government policy, thereby realizing women's empowerment.